NIAT ADOPSI E-COMMERCE WIRAUSAHAWAN MAHASISWA (STUDI PADA MAHASISWA UNS) - Haryanto, Heru Purnomo & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
ABSTRACT This research aims to explore some variables which influence the intention to use (re-use) technology of internet for students who are doing business. This research applied technology acceptance model (TAM) elaborated with theory of planned behavior. Respondents of this research were students of sebelas maret university who have uses internet in their business activities. They were selected by a purposive sampling method. Based on SEM analysis, the result of this research shows that perceived usefulness and subjective norm influence towards intention to use (re-use) technology of internet and also perceived behavioral control and attitude to re-use e-commerce. The result of this research describes that some variables are an antecedent of affective (intention to re-use) in e-commerce. Thus, this result supports the theory of planned behavior by Ajzen and technology acceptance model by Davis. Implications of the findings for developers are discussed further. Keywords: TAM, technology internet, entrepreneurships.